The impact of conflict on asthma - Mohammad, Yousser; Brough, Grace (Journal of Thoracic Disease, 2019)
Asthma is a public health problem worldwide, showing high incidence, high prevalence and causing social and economic damage; this condition may be more prevalent in areas of conflict (1). The evidence on asthma in conflict affected areas and recommendations to improve asthma treatment and prevention are talked about in this editorial.